2019
DOI: 10.3390/jcm8091371
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury and In-Hospital Mortality: A Retrospective Analysis of a Nationwide Administrative Database of Elderly Subjects in Italy

Abstract: Background: The aim of this study was to investigate the association between acute kidney injury (AKI) and in-hospital mortality (IHM) in a large nationwide cohort of elderly subjects in Italy. Methods: We analyzed the hospitalization data of all patients aged ≥65 years, who were discharged with a diagnosis of AKI, which was identified by the presence of the International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM), and extracted from the Italian Health Ministry database (January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Last year, our group demonstrated that in-hospital mortality was a frequent complication in elderly subjects with AKI discharge codes, involving more than a quarter of admissions. The increasing burden of comorbidity, dialysis-dependent AKI, and sepsis were the major risk factors for mortality [ 16 ]. Comorbidity is a well-known risk factor affecting survival in dialysis patients [ 44 ]; however, predictors of short-term survival in renal patients are still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Last year, our group demonstrated that in-hospital mortality was a frequent complication in elderly subjects with AKI discharge codes, involving more than a quarter of admissions. The increasing burden of comorbidity, dialysis-dependent AKI, and sepsis were the major risk factors for mortality [ 16 ]. Comorbidity is a well-known risk factor affecting survival in dialysis patients [ 44 ]; however, predictors of short-term survival in renal patients are still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the debate about clinical impact of the WE effect is still open. Acute kidney injury (AKI) is a frequent finding in hospitalized subjects, especially in people who are 65 years old or older [ 15 , 16 , 17 ]. However, available data about admissions due to renal diseases are scarce; therefore, we wanted to explore the possible relationship between the WE effect and AK by using the National Hospital Database (NHD).…”
Section: Introductionmentioning
confidence: 99%
“…Nephrotoxic AKI was observed in 14.5% of the elderly and was mainly due to use of aminoglycoside and herbal remedies. Nephrotoxicity is linked to 10% -20% of AKI in Cameroonian studies [14] [15] [23]. However, Yao et al, found a lower frequency of nephrotoxic AKI in the elderly (2.8% vs 17%) compared to young adults [11].…”
Section: Discussionmentioning
confidence: 99%
“…[13] [14] comorbid burden was high in our F. M. E. E. H. Danielle et al DOI: 10.4236/ojneph.2020.104031 319 Open Journal of Nephrology population, especially among very elderly patients. As noted in our study, hypertension, diabetes and cardiac disease were the main comorbidities reported [11] [14] [15] [16] [17] [18] and are all associated with renal vasculature damage and compromised renal perfusion.…”
mentioning
confidence: 99%
“…Officially, 17,000 people were killed but very likely the death toll was higher. In total 639 cases of AKI were registered of whom 477 needed dialysis, with a mortality of AE15% [49,50], a low figure compared to standard non-earthquake AKI practice [51]. The experience gained during the earthquake led the foundation for an extensive epidemiological analysis, which was highly helpful to increase objective datadriven knowledge on post-earthquake crush syndrome and AKI.…”
Section: Disaster Relief Interventionsmentioning
confidence: 99%